A NEW COMBINATION IN OROPHEA (ANNONACEAE) FOR UVARIA NITIDA ROXB. EX G. DON - Turner, Ian M. (REINWARDTIA, 2014)
The identity of Uvaria nitida Roxb. ex G.Don. (Annonaceae) has not been considered for 180 years. The plant is only known from material grown in the Calcutta Botanic Garden in India following introduction from, reportedly, the Moluccas. Examination of a specimen from the Brussels Herbarium, designated here as lectotype, indicates that the species is a member of Orophea subgenus Sphaerocarpon, similar to Orophea gabra Merr. A new combination in Orophea is made.